A comprehensive framework for the management of hereditary breast cancers: guiding light in precision medicine - Ekram, Samar; Al Eissa, Mariam M. (Oncology Reviews, 2025)
BackgroundThe landscape of oncology varies across countries and regions, and in consanguineous populations such as Saudi Arabia, the clinical management of hereditary cancers poses a distinct challenge. Hereditary breast cancer (HBC), which is a significant public health concern, accounts for approximately 5%–10% of all breast cancer cases. High-risk genes, including BRCA1, BRCA2, PALB2, TP53 and PTEN, with germline pathogenic or likely pathogenic variants (PVs/LPVs), substantially increase the risk of breast cancer and other malignancies.MethodIn this review, we explore the guidelines and the literature to present a comprehensive investigation of the genetic landscape of hereditary cancer syndromes, provide pivotal insights into disease mechanisms and inform precise clinical intervention. Given their marked therapeutic heterogeneity, a tailored precision medicine approach, rather than a uniform strategy of a one-size-fits-all model, is necessary. For high-risk breast cancer patients in Saudi Arabia, the detection rates of PVs/LPVs have reached 24%, underscoring the relevance of targeted interventions.ResultsA comprehensive framework for the management of HBCs is outlined, which focuses on consanguineous populations and adapts global guidelines. We highlight the critical roles of genetic testing in guiding personalised surveillance strategies, especially for regions where data remain limited.ConclusionRevealing the genetic variation associated with HBCs mitigates the burden on healthcare providers and the long-term effects of HBCs on affected individuals and their families. Moreover, it is a step ahead towards personalised prevention, treatment and intervention. This knowledge will empower research and innovation in biotechnology.